Organizational implementation of educational change: a case of Malaysian open & distance education - Ghavifekr, Simin; Afshari, M.; Siraj, Saedah; Razak, Ahmad Zabidi Abdul (2013)
Nowadays, change management strategies and policies become increasingly important for all organizations including education. This is due to the current market competition and globalization that force organizations to consider “change” as an alternative solution to improve their quality and performance.Organizational implementation of a change process is essential to achieve desired goals and objectives. For educational organizations, especially Open and Distance Learning (ODL) institutions, management strategies and policies for implementing e-learning as an educational systemic change, are believed to be the key answer to improve the quality of teaching and learning processes. This paper is aimed at addressing the key question of “What are the management key strategies and policies for effective organizational implementation of systemic change in context of an ODL organization?” Based on the data analysis for this qualitative research, it was found that in a technology-based systemic change; planning, organizing, guiding and monitoring are the main strategic elements for the management in successful organizational implementation of the new learning technologies. “Organizational implementation” as one of the key components of systemic change management, is the main theme for this study.The results of in-depth analysis including emerged sub-themes and the sub-sub-themes are presented in this paper.